Visual memory and representation of Brazilian rock and Jovem Guarda on long playing album covers (1959-1970) - Vargas, Herom (2020)
Brazilian rock in the 1960s was successful and important for the record companies. Among various media, album covers stand out for representing music, youth and the articulations of memory by photography and design. The aim of this article is to analyze the forms of visual representation of the early Brazilian rock and of the Jovem Guarda on the LP album covers. The corpus consists of 35 artists’ discographies between 1959 and 1970. We apply the notions of representation (Hall, 2016; Lotman, 1998); memory (Halbwachs, 1990; Huyssen, 2001; Pollak, 1989; Bosi, 2003); performance (Zumthor, 2010) and design (Dondis, 2003).